Regeneration of Pinus pinaster forests after wildfire - Castro, José (2013)
Wildfires are of extreme importance in Pinus pinaster forests of central and northern Portugal. Reforestation plans after wildfires are generally made without consideration for the possibility of natural regeneration. This paper addresses the question of the factors responsible for the occurrence of natural regeneration and concludes that litter accumulation, rock outcrops, slope, aspect, harvest, fire characteristics, and stand age are well related to the regeneration observed. Limitations of the model proposed are discussed.